Educational Media in Islamic Perspective - Vikki Wardana; Yesi Martaleni; Dede Arif Rahman Nur Hakim; Opik Taufik Kurahman; Dadan Rusmana (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Learning is a complex process that involves a person physically and mentally throughout his life. The learning process occurs because of the interaction between a person and his environment. Therefore, learning can occur anytime and anywhere. One sign that a person is said to have experienced a learning process is a change in behavior in that person which includes changes in the level of knowledge, skills, and attitudes. The interactions that occur during the learning process are influenced by the environment, which includes students, teachers, librarians, principals, learning materials (books, modules, magazines, video or audio recordings, etc.) and various learning resources and facilities (overhead projectors, radio, television, computers, libraries, etc.). In the teaching and learning process, the presence of media has a fairly important meaning. Because in these activities, the ambiguity of the material presented can be helped by presenting media as an intermediary. Although the initial goal of learning is good, if it is not supported by the right media, this good goal is very difficult to achieve properly. A media in learning will affect whether information is complete and on target or not, and affect the final results of the learning process. However, even so, there are still many educational institutions that are less concerned with the existence of media. It is proven that there are many cases of educators who do not use media in accordance with the material being taught, so that in learning Islamic religious education, students have many difficulties in absorbing and understanding the lessons delivered, Educators have difficulty delivering lesson materials, many students feel bored with Islamic religious education lessons. This can be identified as a problem of lack of understanding of educators in the application of media in the learning process.